An analysis of social science research trends in Sri Lanka from 1975-1984 - Jayasuriya, Sumana C.
At least 94 percent of all researches in the different areas were applied research. Basic research undertaken during the period was comparatively few.
Findings revealed that the output has increased slightly in the latter half of the decade. The most predominant subject areas of research were Economics and Finance, Administrative Science, Sociology and Human Environment. There were hardly any researches in the Behavioral Sciences. Several subject areas of the main subject fields were also found to be neglected by social scientists. Different types of institutions had significantly different outputs by area.
Recommendations were made for the encouragement of research in neglected areas, the training of social scientists in research methodology, the formulation of a national social science research policy, and the development of an information system to maximize the dissemination, utilization and application of research findings.
The data were analyzed to determine the predominant and neglected subject areas of research, predominant methods of research and the educational attainment of the researchers in different research areas.
The educational attainment of the researchers differed with their institutional affiliations. Majority were bachelor's degree holders. A substantial proportion of research was done to obtain higher degrees, thereby increasing the ratio of individual researches to team research.
The prevalent methods of research are the case study, survey method, historical method and a combination of methods. The last two methods were used significantly more in 1980-1984. Researchers in different areas of research tended to favor the use of different methodologies.
This study of 489 social science research studies in Sri Lanka was undertaken to identify research trends for the period 1975-1984.
Mimeographed.
Thesis (M.L.S.)--University of the Philippines, Diliman
Keywords: Social sciences--Sri Lanka--Research.